ASSESSMENT THE KNOWLEDGE OF NURSES ABOUT NEEDLE STICK INJURIES AT AL-ZAHRAA TEACHING HOSPITAL - Duaa Malik; Mubarak Hejab; Mubarak Hejab; Hussain Abd Alrada1 (Central Asian Journal of Medical and Natural Science, 2023)
In Hospitals, Nurses Are The First Level Of The Staff Who Contact With Risk Of Infection From Unsafe Practices Related To Needles And Sharps.They Are Expected To Undertake Activities Related To Patient Care With The Beginning Of Their Clinical Years. Being Amateurs, They Lack Experience And Skill, Therefore; At A Higher Risk Of Infection From Unsafe Practices Related To Needles And Sharps .The Objectives Of The Study Are To Determine Needle Stick Injuries And Their Risks Among Nurses At Al-Zahraa Teaching Hospital And To Provide The Information That Nurses Need To Avoid Needle Stick Injuries And To Assess The Knowledge Of Nurses About Needle Stick Injuries At Al-Zahraa Teaching Hospital The Method Includeincludeed Study Design, Study Population, Setting,Sample (Participants), Sampling Method, Sample Size Tool Of Study,Data Collection, Ethical Considerations, Limitation Of The Study The Results Of The Present Study Suggest That Maybe Most Nurses Have Inadequate Knowledge About Needle Stick Injuries .This Study Concludes That The Needle Stick Injury Is The Most Important Occupational Health Hazard In Nurses With Alarmingly High Rates. This Study Showed That Occasional Needle Injuries By Nurses (72.5%). There Is A High Prevalence Of Cases And Episodes Of Injuries Among Nurses Because They Do Not Fully Practice Standard Precautions, Though They Have Sufficient Knowledge Of Them. Most Nurses Did Not Report The Nsis To The Supervisor Of The Infection Control Unit. This Study Showed That A Majority (85%) Of Them Have Attended Any Training Courses, While Most Of The Participants Shouldn’t Interest By PPE